Study on Failure Characteristics and Reasonable Mining Parameters of Upward Mining of Integrated Coal Mine. (16th June 2022) - Wu, Fengfeng; Lv, Bo; Zhang, Jian; Gao, Zhiqiang; Liu, Shibao; Zhou, Qingcong
Abstract : In order to avoid the problem of repeated repair of roadways in the upper mining area of upward mining in the integrated mine, taking the roadways in the 302 mining area of Shancheng Coal Mine as the research object, the failure characteristics of overlying strata and the evolution characteristics of roadway plastic zone in the mining process of underlying coal seam were studied by combining theoretical analysis, numerical simulation, and engineering measurement. The influence law of underlying coal seam mining on the integrity of 3# coal seam and the stability of roadways in the 302 mining area was revealed, and the repair opportunity of roadways in the upper coal seam and the reasonable position of open-off cut in the lower coal seam working face were determined. The research shows that due to the influence of the mining of the working face in the underlying coal seam, the plastic failure of the overlying strata is serious during the upward mining of Shancheng Coal Mine, but there is no step dislocation, but the overall subsidence is presented. The plastic zone range of roadway in 302 mining area first increases and then tends to be stable with the mining of 97308 working face in underlying coal seam, and the roadway repair should be carried out after 280 m advance of 97308 working face. Based on the coordination between the influence of the cutting position of the underlying coal seam on the variation characteristics of the plastic zone of the upper roadway and the saving of coal resources, it is determined that the cutting position of the underlying 153308 working face is advanced to 340 m. The field engineering application shows that the deformation of roadway surrounding rock meets the production requirements by implementing the above mining parameters, and the rerepair of roadway surrounding rock deformation in 302 mining area of 3# coal seam is avoided.